2011
DOI: 10.1017/s0022215111001848
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial embolisation for paediatric inflammatory pseudotumour of the maxillary sinus

Abstract: This is the first report presenting the utility of arterial embolisation for inflammatory pseudotumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous studies have shown the effectiveness of therapy, such as high-dose corticosteroids, surgical excision, or radiotherapy, for IPTs [ 8 ]. A literature review showed that radiotherapy is proposed for lymphoid-predominant lesions, whereas high-dose corticosteroids may be a better choice for granulomatous lesions [ 12 ]. Our patient had a lymphoid-predominant lesion that responded to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effectiveness of therapy, such as high-dose corticosteroids, surgical excision, or radiotherapy, for IPTs [ 8 ]. A literature review showed that radiotherapy is proposed for lymphoid-predominant lesions, whereas high-dose corticosteroids may be a better choice for granulomatous lesions [ 12 ]. Our patient had a lymphoid-predominant lesion that responded to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another case of maxillary sinus IPT in a 2-year-old girl also had raised ALP (541 IU/L) although no hepatobiliary obstruction was described in that report. [5]…”
mentioning
confidence: 99%